Heydrichia (?) poignantii, sp nov (Sporolithaceae, Sporolithales, Rhodophyta), a 100 million year old fossil coralline red alga from north-eastern Brazil, and a new Hauterivian record of Sporolithon from Switzerland - Woelkerling, William J.; Granier, Bruno; Dias-Brito, Dimas [UNESP] (Carnets Geologie, 2014)
Fossil specimens of Heydrichia (?) poignantii, sp. nov. (Sporolithaceae, Sporolithales, Rhodophyta), representing the first confirmation of the genus in the fossil record, were discovered in thin sections of Albian limestones from the Riachuelo Formation, Sergipe Basin, and in thin sections of Albian -Cenomanian limestones from the Ponta do Mel Formation, Potiguar Basin in north-eastern Brazil. A detailed morphological-anatomical account of the species is provided, and its placement in Heydrichia is discussed in relation to current classification proposals. Comparisons with the four other known species of the genus, all non-fossil, show that H. poignantii is the only known species of Heydrichia in which thalli are encrusting to sparsely warty to horizontally layered with overlapping lamellate branches that commonly appear variously curved or arched, and in which thalli have sporangial complexes that become buried in the thallus. The evolutionary history of Heydrichia remains uncertain, but available data suggest that the genus may have diverged from the sporolithacean genus Sporolithon, known as early as Hauterivian times (c. 129.4-132.9 +/- 1 Ma) from Spain (and newly reported here from Switzerland), or it may have arisen from a graticulacean alga such as Graticula, dating from mid-Silurian times (c. 427-435 Ma). Current data also suggest that Heydrichia is more likely to have arrived in Brazil from Central Atlantic waters than from higher latitude South Atlantic waters. This implies that currently living species in southern Africa probably arose later from ancestors further equatorward in the South Atlantic, although confirming studies are needed. All non-fossil species of Heydrichia are known only from the southern hemisphere.
Keywords: Heydrichia; Sporolithaceae; Sporolithon; fossil coralline red algae; Brazil; Switzerland; Hauterivian; Albian; Cenomanian